The Relationship Between School Principal Leadership Management And Curriculum Development on Students' English Learning Achievement at Sunan Gunungjati Senior High School Tulungagung - Dr. Muh Ibnu Sholeh (PT. Anagata Sembagi Education, 2024)
This research to analyze the relationship between the principal's leadership management on student achievement, the relationship between curriculum development on student learning achievement, and the joint relationship between the principal's leadership management and curriculum development on student learning achievement at Sunan Gunungjati Senior High School Tulungagung . The research method uses a quantitative approach with a population of 55 teachers. Data collection techniques using a questionnaire with a Likert scale were used to provide flexibility in respondent responses. Multiple linear regression analysis technique. The research results showed that there was a positive and significant relationship between principal management and student achievement (R=0.70, p < 0.05). Likewise, curriculum development has a positive and significant relationship with student achievement (R=0.75, p < 0.05). When the two variables were entered together into the regression model, it was confirmed that the combination of principal leadership management and curriculum development made a significant contribution to student achievement (R Square=0.64, p < 0.05). The conclusion of this research shows that efforts to improve principal management and curriculum development can have a significant positive impact on student achievement at Sunan Gunungjati Senior High School Tulungagung . Recommendations for increased investment and attention to principal training and curriculum development are expected to improve the quality of education and student achievement